Money and power : how Goldman Sachs came to rule the world - Cohan, William D. (New York : Doubleday, 2011)
A revelatory history of Goldman Sachs. Reveals how Goldman Sachs has survived financial crises, government investigations, and lawsuits to keep its reputation intact and become one of the most profitable and powerful investment banks in the world.
The Pyrrhic victory -- A family business -- The apostle of prosperity -- The politician -- The value of friendship -- "What is inside information?" -- The biggest man on the block -- Caveat emptor -- The Goldman way -- A formula that works -- Goldman sake -- Busted -- Money -- Power -- The college of cardinals -- $10 billion or bust -- The glorious revolution -- It's too much fun being CEO of Goldman Sachs -- Alchemy -- Getting closer to home -- The fabulous fab -- Selling to widows and orphans -- Meltdown -- Goldman gets paid -- God's work.
Includes bibliographical references (p. [615]-630) and index.
oif 17/09/14
Loan
Keywords: Goldman, Sachs & Co; Investment banking -- United States; Going public (Securities); Banks and banking -- United States; Investments -- United States; Securities